Factors associated with the activities of safety representatives in Spanish workplaces. Issue 9 (14th August 2007) - García, Ana M; López-Jacob, Maria José; Dudzinski, Isabel; Gadea, Rafael; Rodrigo, Fernando
Abstract : Objective: To describe the activities of safety representatives in workplaces in Spain. Methods: A specific questionnaire was applied to a representative sample of safety representatives. Activities developed during the past year, presented in a closed ended list, were categorised into three groups: information and advising; participation in occupational health management; and pressure on or negotiation with employers. Personal phone interviews were conducted from September to December 2004. A sample of 1201 interviews was attained. Crude and multivariate analyses were carried out. Results: Spanish safety representatives were mostly men (76%), aged 26 to 45 years (62%), with fixed contracts (94%), and more than 10 years in their company (57%). On a comparable 0–10 scale, the mean (95% confidence interval (CI)) number of activities relating to information, management, and negotiation developed during the previous year were, respectively, 6.8 (6.7 to 6.9), 4.5 (4.4 to 4.7), and 4.0 (3.8 to 4.1). In multivariate analysis, workplace size (>30 workers), industrial sector, training, and support from the labour inspectorate were the factors most consistently associated with safety representatives' activity. Additionally, support from the employer was associated with participation in occupational health management (odds ratio = 2.38 (95% CI, 1.73 to 3.29)). Conclusions: Safety representatives in Spain have a variety of activities, mostly in the category of information and advising. These are necessary but not sufficient for real participation of workers in decisions concerning their health and safety. More participation of safety representatives in occupational health management at workplaces seems to be needed, and factors associated with this participation reinforced.